Efficiency of the environmental licensing process in mining exploration in Marabá: A case study (Research, Society and Development, 2021)
The growth of the mining industry in the state of Pará has shown not only economic benefits, but mainly environmental losses due to the exploitation of manganese ore in the region. In this sense, one of the most important instruments used by the State to manage and exercise control over activities that interfere with the environment is environmental licensing. Procedures for obtaining environmental licenses have become increasingly required in accordance with the requirements of the responsible bodies, which is generated by the wide discussion in the political environment regarding a real licensing process. In this aspect, this article presents itself as an exploratory study, based on the documentary analysis of four enterprises with the objective of efficiency of the environmental process within the scope of Public Administration in the municipality of Marabá. The method used in the research focused on the application of checklists. The flaws observed within the public machinery as well as deficient environmental studies influence the dynamics of the process, culminating in a mostly bureaucratic environmental licensing process.